Editorial review: American Journal of Sports Medicine “Anatomic Reconstruction of the Anterior Cruciate Ligament of the Knee With or Without Reconstruction of the Anterolateral Ligament” - Ekhtiari, Seper; Coughlin, Ryan P.; Ayeni, Olufemi R. (Annals of Joint, 2018)
Since it was first described (though not named) by Dr. Segond in the context of his eponymous fracture in 1879 (1), the anterolateral ligament (ALL) of the knee has drawn limited attention through the years. More recently, however, there has been a renewed interest in the de nition and study of the ALL (2). While exact descriptions vary between cadaveric studies, it is universally described as originating from the lateral femoral condyle and inserting into the anterolateral part of the proximal tibia, midway between Gerdy’s tubercle and the head of the fibula (3). Biomechanical studies have revealed it to be a stabilizer of the knee joint in internal rotation, with its maximal stabilizing effect seen between 30 and 90 degrees of exion depending on the study (3).